Successful management of hypothyroidism symptoms with Shankh Mudra: A Case Study - Dr. Preeti Joshi1, Dr. Gaurav Phull2, Dr. Mohan Rao3 (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Hypothyroidism is one of the most common endocrine diseases. When the production of thyroid hormone is reduced it is termed as hypothyroidism. Impairment of the thyroid function is normally associated with variations in body weight and composition, temperature of the body, along with total and resting energy expenditure, as the triiodothyronine regulates the normal metabolism and thermogenesis and thereby plays a more crucial role in the metabolism pathways such as the glucose and lipid metabolism, and also food intake, and the fatty acid oxidation1. The prevalence of hypothyroidism in India is 11%2.